Entrepreneurship education - Jones, Paul, 1954-; Maas, G. 1959-; Pittaway, Luke (Contemporary issues in entrepreneurship research ;, 2017)
Universities globally are under pressure from an expanding range of stakeholders to provide enterprise education and support to students. Enterprise education had become a research domain in itself and an increasingly important aspect of UK universities' curricular. Within the UK, policymakers consider enterprise education, and the skills it develops, as increasing student's employability skills, regardless of what their primary subject of study is, and thereby assisting them in gaining employment upon. Despite this growth, there is ongoing debate regarding the effectiveness of entrepreneurship education and there are calls for further evidence to validate its impact. This book meets that call in providing further evidence for best practice and successful deployment. Authors provide evidence to inform the entrepreneurial education discipline in terms of best practice, success stories and identify its future direction for key stakeholders. The book concludes with a summary from the authors which will analyse and contrast the emergent themes identified in each chapter.